The Improvement of Students' Speaking and Listening Skills Through TikTok Native Speakers' Videos of the Eleventh Grade of F Senior High School 1 Girimarto in the Academic Year of 2025/2026 - Suwati Suwati; Hersulastuti Hersulastuti; Endang Eko Djati (EduInovasi: Journal of Basic Educational Studies, 2026)
This research aimed to improve students’ learning outcomes through the implementation of TikTok-based learning. The research was conducted using Classroom Action Research (CAR) involving 35 students as the participants. The study was carried out in two main stages, namely the pre-test and the implementation of the learning treatment followed by the post-test. The purpose of the pre-test was to identify the students’ initial ability before the implementation of TikTok-based learning, while the post-test was conducted to measure the improvement in students’ learning outcomes after the treatment. The results of the pre-test showed that the students’ mean score was 71, which indicates that students’ understanding of the learning material was still relatively moderate. Although some students achieved the Minimum Mastery Criterion (KKM) of 70, several students still obtained scores below the required standard. This condition showed that students still needed improvement in their learning outcomes. After the implementation of TikTok-based learning in the learning process, the post-test results showed a significant improvement in students’ achievement. The mean score increased to 86.57, which indicates a considerable improvement compared to the pre-test results. In addition, most students were able to achieve scores above the Minimum Mastery Criterion, indicating that the learning objectives were successfully achieved. Based on the findings of this research, it can be concluded that the implementation of TikTok-based learning can effectively improve students’ learning outcomes. The use of short and engaging educational videos helps increase students’ motivation, engagement, and understanding of the learning material.